PENGARUH PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 5 PONTIANAK - Rahmawati, Rahmawati; Melati, Husna Amalya; Putra, Rody (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the differences in learning outcomes between students taught with a cooperative type snowball throwing model with students taught by the lecture method on atomic structure material tenth grade of SMAN 5 Pontianak. The form of this research is Quasy Experimental Designs with the research design of Nonequivalent Control Group Design. The research sample was XH class students as the control class and XF as the experimental class. Based on data analysis using the U-Mann Whitney test, the Asymp value was obtained. sig ((2-tailed) 0.024 or Asymp. sig ((2-tailed) <0.05, so Ha is accepted and Ho is rejected which means there are differences in learning outcomes between control class students and experimental class students on atomic structure material. Learning using a cooperative model snowball throwing type has a high influence with a value of effect size of 0.96.This shows that learning using a cooperative model snowball throwing type can improve student learning outcomes in learning the atomic structure material in tenth grade of SMAN 5 Pontianak.Keywords: Cooperative Learning, Snowball Throwing, Atomic Structure